The burden of infective encephalitis in children in Asian countries (1990–2021): systematic analysis and projection of the burden of disease - Luo, Yonghan; Feng, Yuemei; Wang, Yanchun; Yang, Xiaotao; Guo, Yan; Feng, Yue; Xia, Xueshan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundInfective encephalitis (IE) constitutes a severe neurological disorder with considerable morbidity and mortality among children, particularly in Asia, where stark disparities in socioeconomic status and healthcare accessibility prevail. Despite its substantial impact, comprehensive epidemiological investigations into pediatric IE across Asia remain scarce.ObjectiveThis study aimed to systematically evaluate the burden of pediatric IE in Asia from 1990 to 2021, examine its association with sociodemographic development, identify major risk factors, and forecast future trends.MethodsUtilizing data from the Global Burden of Disease (GBD) 2021 study, we retrieved incidence, mortality, and disability-adjusted life years (DALYs) for individuals aged 0–14 years across six Asian regions and more than 50 countries. Statistical methods included trend analysis via estimated annual percentage change (EAPC), Spearman’s correlation between disease burden and the Sociodemographic Index (SDI), and decomposition of risk factors. A Bayesian Age-Period-Cohort (BAPC) model was employed to project trends in China, Japan, South Korea, and India from 2022 to 2035.ResultsIn 2021, Asia recorded 537,750 IE cases (49.3 per 100,000), 18,844 deaths (1.7 per 100,000), and 1.69 million DALYs (155.1 per 100,000). Between 1990 and 2021, there were substantial reductions in the burden of IE: incidence declined by 28.1% (from 68.6 to 49.3 per 100,000), mortality by 53.2% (from 3.7 to 1.7 per 100,000), and DALYs by 53.2% (from 331.0 to 155.1 per 100,000). South Asia exhibited the highest burden (71.7 incidence, 2.5 mortality, 226.7 DALYs per 100,000), whereas the High-income Asia Pacific region reported the lowest (11.7, 0.1, 11.6 per 100,000). SDI demonstrated strong inverse correlations with incidence (r = −0.73), mortality (r = −0.87), and DALYs (r = −0.87). Low birth weight/prematurity and particulate matter pollution emerged as principal risk factors. Forecasts suggest continued declines by 2035, with India and China projected to see the most pronounced reductions in incidence (−62.4% and −41.3%, respectively).ConclusionAlthough the burden of IE has markedly declined since 1990, it remains a pressing public health concern in low-SDI Asian regions. Focused strategies addressing undernutrition, environmental hazards, and neonatal health are imperative.